2007
DOI: 10.1111/j.1863-2378.2007.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Salmonella Typhimurium in Bovine Diarrhoeic Fecal Samples by Immunomagnetic Separation and Multiplex PCR Assay

Abstract: The aim of this study was to use the immunomagnetic separation (IMS) test plus a multiplex polymerase chain reaction (m-PCR) assay to detect Salmonella at genus level and also for the identification of Salmonella enterica serovar Typhimurium in bovine diarrhoeic fecal samples. In all, 400 bovine diarrhoeic fecal specimens were examined by conventional bacterial culture, IMS, and m-PCR. For m-PCR assay, four set primers were selected: 139-141, specific for inv-A gene of Salmonella spp and the RfbJ, FliC and Flj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…For S. Typhimurium, PCR assays were published targeting the O and H1, H2 antigen-encoding genes (Salehi et al 2007;Lim et al 2003;Soumet et al 1999) or other genes predominantly found in the genome of this serovar (Kim et al 2006a). S. Typhimurium-specific real-time PCRbased assays were not found in literature.…”
Section: Pcr-based Serovar-specific Identification Methodsmentioning
confidence: 99%
“…For S. Typhimurium, PCR assays were published targeting the O and H1, H2 antigen-encoding genes (Salehi et al 2007;Lim et al 2003;Soumet et al 1999) or other genes predominantly found in the genome of this serovar (Kim et al 2006a). S. Typhimurium-specific real-time PCRbased assays were not found in literature.…”
Section: Pcr-based Serovar-specific Identification Methodsmentioning
confidence: 99%
“…Three to four suspected colonies were chosen and subcultured, and the isolates were confirmed as E coli by conventional biochemical tests. Total genomic DNA was extracted from overnight cultures on Luria Bertani agar (Merck) by the boiling method, as described by Zahraei Salehi and others (2007), and the supernatant was subsequently used as the template in the PCR mixture. All E coli isolates were screened by multiplex PCR using four pairs of specific primers for stx1, stx2, eae and Ehly (Paton and Paton 1998a).…”
Section: Methodsmentioning
confidence: 99%
“…All effective molecular detection methods (such as PCR based methods and isothermal methods) require target genes. The target genes inv A, ttr RSBCA (operon including 5 genes of ttr R, ttr S, ttr B, ttr C, ttr A), pho P, fim A, agf A, and spv C have been frequently used either separately or in combination for Salmonella detection in many PCR and loop-mediated isothermal amplification (LAMP) assays 8 18 . All these target genes are located on chromosome, except for spv C, which is encoded on a plasmid.…”
Section: Introductionmentioning
confidence: 99%